(untitled) (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
The development of Internet of Things (IoT) technology has driven the implementation of smart home systems that require real-time, efficient, and reliable data communication. Wireless Sensor Networks (WSN) are an important component in environmental data collection, but their implementation still faces challenges related to network reliability, response time, and wireless communication stability. This study aims to implement and evaluate the performance of a WSN- and IoT-based smart home system in supporting real-time environmental condition monitoring and home device control. This study uses an experimental method by designing and implementing a WSN architecture integrated with an IoT platform. The system consists of several sensor nodes, an IoT gateway, and a web-based monitoring dashboard. Testing was conducted to observe sensor data transmission, system response time, and wireless network connection stability. The results showed that temperature and humidity sensor data were successfully transmitted periodically and displayed in real-time on the monitoring dashboard. The system demonstrated a high level of data transmission reliability, relatively short response times, and stable network connections during testing with several active sensor nodes. The dashboard is also capable of consistently displaying the status of sensor nodes and smart home devices. The implementation of IoT-based WSN has proven to be effective in supporting smart home systems for monitoring and controlling the home environment. The developed system meets the basic requirements of real-time monitoring and has the potential for further development through the addition of sensors, improved network security, and integration of other smart services in future research.